The Influence of Per Capita Income, Human Development Index, and Unemployment Rate on Poverty Levels in North Sumatra - Nasution, Kautsar Fatin Dharmawan; Hasibuan, Andriansyah; Ananda, Bunga; Sitohang, Cindy Eleonora; Fayza, Salsabila; Nasution, Armin Rahmansyah (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
North Sumatra, a province abundant in economic potential and natural resources, still grapples with severe poverty. This phenomenon of poverty is not influenced by a single factor but by a multitude of interrelated economic variables. In this study, data collection is carried out secondarily, utilizing up-to-date data from the Central Bureau of Statistics. The research method employed is descriptive quantitative. From the analysis, it is evident that the R Square value stands at 0.991. This indicates that the variables of Income per Capita (X1), Human Development Index (X2), and Unemployment Rate (X3) collectively influence the Poverty Level (Y) by 99.1%. The decision-making process can be informed by the time span of the data or the specific areas from which the data is derived. Despite North Sumatra’s rich resources, poverty remains a significant issue, underlining the complexity and interplay of various economic factors. The high R Square value suggests a strong correlation between income, human development, and employment levels in determining poverty. This comprehensive understanding emphasizes the necessity for targeted policies that address these interlinked factors to effectively combat poverty in the region. By analyzing secondary data from credible sources, the study highlights the importance of a multifaceted approach in addressing poverty. The insights derived from the data can guide policymakers in formulating strategies that not only boost economic growth but also ensure equitable development, thereby reducing poverty levels. The findings underscore the critical need for continuous monitoring and analysis of these economic variables to foster sustainable development in North Sumatra.